Development of an Intelligent Decision Support System for Flood Mitigation in the Pahang River - Saher, Faisal Nadeem; Nasly, Mohamed Ali; Wan Faizal, Wan Ishak; Mohd Abdul Nassir, Bidin (Science Target, 2014)
This is an established truth that with the growing world, the flood hazards cannot be avoided but the technology is a solution to minimize this process. A sustainable development depends on plans, which are designed on the strong basis of comprehensive datasets. Managing river is an acute and more attentive area where it faces heavy water feeds due to rains. Malaysia is going on fast development including infrastructural developments and change of land uses from forest cover to other non-green land uses. Adopting innovative products for flood mitigation are required as an integral part of local design transformation. Keeping this fact in view, the vulnerability which may cause due to floods in Pahang River seems to be a threat for the sustainable development of the area. The general objective of this study was to propose a visual aided decision support platform providing an ease but acceptable level of strategy. Presented prototype includes modelling and GIS based visual aids. A study of Pahang River in Malaysia conducted, to explain the applications of the prototype. To achieve this goal a geodatabase, consisting of different hydro-informatics data layers, has been developed. Further work on modified models for better forecasting under real time data input and design of innovative self-protecting flood mitigation at industrial and house hold level is identified as future research area. Under this research studies, the required datasets were generated using remote sensing and GIS system integrated with field GPS surveys. The methodology adopted to achieve the desired goals and to combat the complexity of the hydro-geodatabase of Pahang River drawn from the idea to integrate the engineering tools with the geo-informatics techniques